The Invisible Killer of the Operating Room: How Surgical Smoke Acts as a Toxic Airborne Threat to the Respiratory Fitness, Oncogenic Risk Profile and Occupational Safety of the Surgical Team - Szepietowska, Martyna; Janik, Dominika; Zapart, Zuzanna; Sochocka, Agata; Nowicka, Nina; Gańska, Oliwia Zuzanna; Sikorska, Alicja; Bundyra, Jakub; Mian, Emil; Parda, Julia (Quality in Sport, 2026)
Background. Surgical smoke is a hazardous byproduct generated by energy-based devices such as electrocautery, lasers, and ultrasonic scalpels during thermal tissue ablation. While water vapor accounts for most of the plume, the remaining portion contains chemical pollutants, particulate matter, and infectious biological agents that may affect the physical health of the surgical team. Operating room personnel are frequently exposed to these substances due to inconsistent safety standards. Aim. This review analyses the chemical, physical, and biological hazards associated with surgical smoke and evaluates documented health outcomes among surgical personnel and the efficacy of modern protective and evacuation measures. Material and methods. A review of literature was conducted using PubMed and Google Scholar, with a focus on English-language publications that addressed the chemical and biological composition of the smoke, clinical health outcomes, and the technological efficiency of various filtration and evacuation systems. Results. Research consistently indicates that surgical plume contains carcinogenic and toxic substances, such as benzene and formaldehyde in concentrations that can exceed occupational exposure limits. Significant evidence shows the potential aerosolization of pathogens such as HPV, Hepatitis B, and coronaviruses. Chronic exposure is associated with a higher risk of severe persistent asthma and various acute symptoms, as well as specific head and neck cancers. While standard surgical masks provide inadequate filtration for submicron particles, N95 respirators and integrated smoke evacuation systems show high capture efficiency. Conclusions. Surgical smoke represents a substantial oncogenic and infectious risk to operating room staff. To mitigate these hazards, institutional mandates for the use of smoke evacuation technology are necessary, alongside targeted education to improve staff compliance and safety behaviours.